Nanoquasicrystalline Al-Fe-Cr-based alloys with high strength at elevated temperature - Galano, M; Audebert, F; Garcia Escorial, A; Stone, I; Cantor, B (2010)
Nanoquasicrystalline Al-Fe-Cr-based alloys have a microstructure composed of nanoquasicrystalline particles embedded in an α-Al matrix, and have high strength at elevated temperatures. However, the metastability of the quasicrystalline phase can limit the use of these alloys at elevated temperatures. The microstructure, stability and mechanical properties at different temperatures on melt-spun nanoquasicrystalline Al-Fe-Cr-based alloys containing Ti, V, Nb or Ta have been studied and summarized in the present work. The structural characterisation was carried out by means of X-ray diffraction, hot-stage transmission electron microscopy and scanning-transmission electron microscopy. The addition of a fourth element to the Al93(Fe3Cr2)7 alloy increases the thermal stability, in particular in the case of the Nb and Ta containing alloys, leading to the delay of the phase transformation towards the melting of the alloys. The mechanical properties at elevated temperatures were studied by tensile tests at different test temperatures with different pre-heat treatments. All the alloys showed a very high strength up to 350 °C, more than five times the strength of the commercial Al alloys. These values and the enhanced thermal stability achieved in the quaternary nanoquasicrystalline Al-Fe-Cr-(Ti, V, Nb or Ta) alloys make these alloys very promising for industrial applications. © 2009 Elsevier B.V. All rights reserved.